Uniaxial tension and compression studies on cement clinkers using molecular dynamic simulations - Alex, Aleena; Sindu, B. S.; Sasmal, Saptarshi (Journal of Structural Engineering, 2025)
Techniques such as Molecular Dynamic Simulation and ab initio methods have redefined the paradigm of looking at materials, properties and processes in atomistic and molecular level. Cementitious materials, with their complicated chemistry and microstructure can be better evaluated using these techniques. The studies on the structure and properties of basic components of ordinary Portland cement aims at understanding its strength characteristics. This paper aims at obtaining the mechanical properties of two cement clinkers: Tri calcium aluminate (C₃A) responsible for the setting and hardening, and Dicalcium silicate (C₂S) responsible for the later strength development. Molecular Dynamic simulations are carried out on these and the stress-strain relationships of the cement clinkers are obtained under both uniaxial tensile and compressive loading. Consistent Valance Force Field (CVFF) is used for the study of C₃A and COMPASS forcefield for C₂S. Molecular Dynamic (MD) simulations are carried out using LAMMPS. The results obtained from this MD simulation studies will be helpful for evaluating the multi scale behavior- and for further engineering- the composite materials like concrete. It is also useful to study the relative merits of various force fields to determine the stability of simulations and accuracy of the parameters used. The relative influence of various interaction potentials are also discussed in the study.